(untitled) (Research, Society and Development, 2020)
This article purposes to analyze the arising of President João Pessoa Agricultural Center (Pindobal) under the light of Nova doctrine’s percepts, in the mid of 1930’s, at the Paraíba state. The methodological ways we walked have documental character and qualitative base, using the prints as the primary research source, starting by the Paradigm and the Speech Analysis to explore the creation of Pindobal. In a pragmatic way, the results are based on the affirmation that Pindobal is an institution thought from two perspectives: the one of professional agricultural education and the one of correction for possible deviations in conduct, culminating in incarceration to civilize. That institution was created to support young people in situation of social vulnerability and, according to the prints, assumes the purpose of socialize the useful teaching to misguided children. We also point that the institution assumes Escolanovismo’s elements, the one that the director Sizenando Costa makes harsh criticisms to bookish teachings models and defends a teahing for work and life.